2021
DOI: 10.3390/ma14092199
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Experiments of Particle Mixing Process with the SPH-DEM Model

Abstract: Particle mixing process is critical for the design and quality control of concrete and composite production. This paper develops an algorithm to simulate the high-shear mixing process of a granular flow containing a high proportion of solid particles mixed in a liquid. DEM is employed to simulate solid particle interactions; whereas SPH is implemented to simulate the liquid particles. The two-way coupling force between SPH and DEM particles is used to evaluate the solid-liquid interaction of a multi-phase flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…They found that mixing homogeneity is highly dependent on liquid content, and a transition to viscoplastic behavior occurs at a critical liquid content. Zhu et al [15] focused on the high-shear mixing process of a granular flow containing a high proportion of solid particles in a liquid. Their study demonstrated that a higher moisture content tends to slow down the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…They found that mixing homogeneity is highly dependent on liquid content, and a transition to viscoplastic behavior occurs at a critical liquid content. Zhu et al [15] focused on the high-shear mixing process of a granular flow containing a high proportion of solid particles in a liquid. Their study demonstrated that a higher moisture content tends to slow down the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is the largest material and part used in building construction [1], and its quality has a significant impact on the quality of building construction [2], such as bridges, airports, roads, and military defenses. Concrete is usually made of coarse aggregate, gravel [3,4], cement, and other materials in appropriate proportions, relying on a horizontal shaft mixing device and the selection of appropriate mixing parameters [5][6][7] to complete its mixing production process. Therefore, the quality of concrete often depends on various factors such as device structural parameters, mixing parameters, and material characteristics during the mixing process [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, in which the authors compare the results obtained by the above methods, are available [26][27][28][29][30][31][32][33]. Taking into account that due to the bird strike, large deformations to the bird occur, the mesh-less SPH method is the most suitable [34][35][36]. The SPH technique was used in numerical methods to avoid the constraints related to the distortion of the finite element mesh when solving problems with strong deformations.…”
Section: Introductionmentioning
confidence: 99%